Modelling and simulation of improved scarani-acin-ribordy-GISIN-04 preprocessing technique - Mohd Nasir, Rinie Narinie (2015)
Quantum Key Distribution (QKD) can be considered as the best secured technol- ogy that appreciates the quantum mechanics principals in terms of information transmission over vulnerable quantum channel. QKD ensures that both parties can share the matched secret key through particular designated method in order to protect the shared key from the intruders to eavesdrop the information. Every procedure needs its own protocol to carry out the work accordingly and there are many QKD protocols in the quantum system that can be used in the transmission. In this study, the Scarani, Acin, Ribordy and Gisin 2004 (SARG04) protocol has been choosen because of its robustness against Photon Number Split- ting (PNS) attack compared to Bennet and Brassard 1984 (BB84) protocol. It is more likely that by improving secret key rate, the system can be more robust. Therefore, enhancing the secret key rate is one of the best way to enhance the security and authentication of the communication system. The Improved SARG04 (ISARG04) was introduced in a thesis by Ghazali (2012) in order to enhance secret key rate and its confidentiality from unauthorized parties. However, the studies were not being compared with SARG04 preprocessing technique. Therefore in this study, a mathematical modeling and a comparison between the secret key rate of the preprocessing of the existing SARG04 and the proposed technique of ISARG04 will be investigated in more details.The results of this study show that the preprocessing technique of ISARG04 pro- tocol is robust within the range of Quantum Bit Error Rate (QBER) between 0:14625 and 0:14880. The ratio of secret key rate between ISARG04 and SARG04 is exceeds one, hence the modification is improved. This outcome has shown an improved secret key rate against PNS attack. In consequence, it is expected that this study will bring an aspiration and contribution for future QKD protocol.